Informação em acervos de C&T: mediação científica e a coleção Claude Henri Gorceix - Carlos Augusto Ribeiro Jotta (2015)
The presented paper seeks to analyze the scientific mediation strategy at Science and Technical Museum - School of Mines, Federal University of Ouro Preto by using the Information Management as field of analysis. It is a study case about the Collection of Scientific Instruments Claude Henri Gorceix, founder of the School of Mines of Ouro Preto, where the museum is located. This paper seeks to answer the question: how does the information management in collections musealized of science and technology interferes on the strategies of scientific mediation within the museums that possess these collections? By analyzing three categories: function, significance and museological context of the objects present in the collection, the information will be gathered and systematized, in order to contribute to the scientific mediation strategies used on the exhibitions of this collection.